(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Decline in cholinergic function and oxidative/nitrosative stress play a central role in Alzheimer’s disease (AD). Previous quantitative HPLC profiling analysis has revealed the presence of Pinostrobin, formononetin, vitexin and other neuroprotective flavonoids in Cajanus cajan seed extract. This study was designed to investigate the protective action of Cajanus cajan ethanol seed extract (CC) on learning and memory functions using scopolamine mouse model of amnesia. Materials and methods: Adult mice were pretreated with CC (50, 100, or 200mg/kg, p.o) or vehicle (10ml/kg, p.o) for 16 days consecutively. Scopolamine, a competitive muscarinic cholinergic receptor antagonist (1mg/kg, i.p.) was given an hour after CC pretreatment from days 3 to 16. The mice were subjected to behavioural tests from day 11 (open field test (OFT)/ Y-maze test (YMT) and Morris water maze task (MWM) from days 12-16. Animals were euthanized 1h after behavioral test on day 16 and discrete brain regions isolated for markers of oxidative stress and cholinergic signaling. Molecular docking analysis was undertaken to predict the possible mechanism(s) of CC-induced anti-amnesic action. pre-administration of CC significantly reversed working memory and learning deficits caused by scopolamine in YMT and MWM tests, respectively. Moreover, CC prevented scopolamine-induced oxidative and nitrosative stress radicals in the hippocampus evidenced in significant increase in glutathione (GSH) level, superoxide dismutase (SOD) and catalase (CAT) activities with a marked decrease in malondialdehyde (MDA) production, as well as significant inhibition of hippocampal scopolamine-induced increase in acetylcholinesterase activity by CC. The molecular docking analysis showed that out of the 19 compounds, the following had the highest binding affinity; Pinostrobin (-8.7 Kcal/mol), friedeline (-7.5kCal/mol), and lupeol (-8.2 Kcal/mol), respectively, to neuronal muscarinic M1 acetylcholine receptor, α7 nicotinic acetylcholine receptor and amyloid beta peptide binding pockets, which further supports the ability of CC to enhance neuronal cholinergic signaling and possible inhibition of amyloid beta aggregation. This study showed that Cajanus cajan seeds extract improved working memory and learning through enhancement of cholinergic signaling, antioxidant capacity and reduction in amyloidogenesis.